ChemInform Abstract: Concise Synthesis of Acetal‐Protected syn 1, 3‐Diols by a Tandem Hemiacetal Formation/Tsuji—Trost Reaction. Issue 9 (5th March 2013) - Wang, Liang; Menche, Dirk
Abstract A novel domino sequence for synthesis of the title compounds is developed.